Comparative evaluation of revised trauma score and injury severity score as prognosis predictor among polytrauma patients - Diwakar Verma; Nitesh Kumar; Anshul Jain; Binod Krishna Gouda; Suman Kumawat (Archives of Trauma Research, 2021)
Background and Objectives: The trauma is a major reason for various disabilities and even death around the world. Prompt actions and appropriate management are needed to minimize the level of injuries and mortality. An effective tool is needed to assess the prognosis of the patient in trauma. The objective of the study was to compare the evaluation of RTS and injury severity score (ISS) as a prognosis predictor among trauma patients. Methodology: A cross-sectional clinical observational study was conducted in the emergency department. A total of 88 samples were selected by random sampling technique. The data collection was done using demographic and clinical tools, Glasgow Coma Scale, Revised Trauma Score (RTS), and ISS. Data analysis was performed using SPSS 18. Results: In the present study, the majority of the participants (79.54%) were male. The most common mode of injury among the patients was road traffic accidents (54.54%) with blunt trauma. The findings revealed a negative correlation (‒0.368) between RTS and ISS scores with significant P = 0.0004. RTS (<10) and ISS (≥20) have significant association with mortality and hospital stay. The sensitivities of ISS and RTS with mortality were 84.2% and 89.4%, respectively. Conclusion: RTS is a comparatively better predictor of prognosis than ISS among trauma patients. Lower RTS and higher ISS are significantly associated with mortality and long hospital stay. Early evaluation of the injury level can be effective in patient management.